Determinación de procedimientos para la localización de fallas en redes eléctricas soterradas de medio voltaje utilizando el sistema Megger Centrix 2.0 de la Empresa Eléctrica Quito. - Chancusig Chiliguano, Kevin Giovanny (2021)
Every electric power distribution company that has medium voltage underground networks is exposed to a failure in any part of it, which is why implementing new technologies with their respective procedures is essential to ensure its reliability and quality of service. In this project, the procedures to be followed for the location of faults in medium voltage subway electrical cables using Megger Centrix 2.0 system equipment were elaborated. First of all, a bibliographic compilation of all the aspects involved in the search for a fault in medium voltage underground distribution networks was carried out. Then, in order to validate the methods used to guide the system, a field test was performed in a distribution network belonging to Empresa Eléctrica Quito (EEQ) and it was proposed to perform simulations based on standards such as IEEE Std 1234-2019, using PSCAD software for TDR analysis (reflectometry in the time domain), while Matlab - Simulink software was used for precise acoustic location, implementing its characteristic circuits. Finally as results were obtained percentages of error between the field measurement and the high simulation but in spite of this it was possible to demonstrate that the principle of operation of the equipment used are present in the simulations performed, everything mentioned above is summarized in the data tables that contain each of the tests at the end of the simulated methods.